Design And Development Of An N8N-Based Ai Chatbot System Integrated With Whatsapp As An Information Service At Maxy Academy - Chiboy Cristian Sibarani; Bonda Sisephaputra (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Maxy Academy experiences operational inefficiency due to the high volume of customer inquiries on WhatsApp being handled manually. This study aims to design and develop an automated information service solution using an n8n-based AI Chatbot integrated with WhatsApp. Utilizing a Research and Development (R&D) approach with a Rapid Application Development (RAD) model, the system architecture incorporates the n8n orchestrator, WhatsApp HTTP API (WAHA), Large Language Model (LLM) agents, and a PERN Stack-based operational dashboard. The developed system successfully operates 24/7, proactively extracts customer data, and facilitates a silent handover mechanism for human agent intervention. Functional evaluation using Black Box Testing demonstrated a 100% validity rate across all test scenarios, confirming the software’s functional reliability without any defects. The R&D process successfully produced a stable and responsive automated information service that effectively classifies message queues.